2005
DOI: 10.1007/s10709-004-2281-3
|View full text |Cite
|
Sign up to set email alerts
|

Conserved 5S and variable 45S rDNA chromosomal localisation revealed by FISH in Astyanax scabripinnis (Pisces, Characidae)

Abstract: Fluorescence in situ hybridisation (FISH) and double FISH experiments were carried out to ascertain the chromosomal distribution pattern of the 45S and 5S ribosomal (r) DNAs in four populations of the characid fish Astyanax scabripinnis--a group considered to be a species complex for its wide karyotypical and morphological diversity. The results regarding the 45S rDNA agreed with this hypothesis, since these sites showed intra- and inter-populational, numerical and positional variations. However, the data obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
91
2
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(112 citation statements)
references
References 33 publications
18
91
2
1
Order By: Relevance
“…The number and location of the 18S rDNA sites in Astyanax is considered variable and multiple (Néo et al, 2000;Ferro et al, 2001;Mantovani et al, 2005 andVicari et al, 2008a), dispersed by karyotypes mainly through transposition mechanisms (Fernandes & Martins-Santos, 2006;Vicari et al, 2008b). The two populations from Ribeirão Grande analyzed in the present study corroborated with the condition of multiple 18S rDNA sites found in other Astyanax.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The number and location of the 18S rDNA sites in Astyanax is considered variable and multiple (Néo et al, 2000;Ferro et al, 2001;Mantovani et al, 2005 andVicari et al, 2008a), dispersed by karyotypes mainly through transposition mechanisms (Fernandes & Martins-Santos, 2006;Vicari et al, 2008b). The two populations from Ribeirão Grande analyzed in the present study corroborated with the condition of multiple 18S rDNA sites found in other Astyanax.…”
Section: Discussionsupporting
confidence: 86%
“…In relation to 5S rDNA, this tended to be more conserved in Astyanax, being predominantly located in the proximal region of an acrocentric pair and a metacentric pair (Ferro et al, 2001;Almeida-Toledo et al, 2002;Mantovani et al, 2005;Vicari et al, 2008a). However, the occurrence of more chromosome pairs carrying this rDNA has been registered (Ferro et al, 2001;Vicari et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, these variations have been confirmed by the use of fluorescent in situ hybridization (FISH) with 18S rDNA probes (Kavalco et al, 2005;Mantovani et al, 2005;Pazza et al, 2006). However, structural polymorphisms due to other chromosomal rearrangements such as inversions and centric fusions/ fissions are not very common among Neotropical fish, being known mainly among Characiformes (Giuliano-Caetano & Bertollo, 1988;Cestari & Galetti Jr.,1992;Centofante et al, 2002;Jorge & Moreira Filho, 2004;Pazza et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Herein, an extensive intrapopulational polymorphism of 18S rDNA sites in several karyomorphs was detected and seems to be related to the association of these sequences with transposable elements or with their telomeric position, which would facilitate the transference of this material during interphase (Foresti et al, 1981;Mantovani et al, 2005). Furthermore, these polymorphic differences have also been detected in other Synbranchus species (Carvalho et al, 2012), suggesting that this is a common characteristic in this group of organisms.…”
Section: Discussionmentioning
confidence: 67%